Artificial Intelligence and Data Science Based R&D Interventions Proceedings of NERC 2022 - Bhattacharjee, Ratnajit; Neog, Debanga Raj.; Mopuri, Konda Reddy; Vipparthi, Santosh Kumar (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book title is a composition of multiple research efforts that are based on cutting-edge Artificial Intelligence (AI) techniques. Some of the signal processing problems are addressed with techniques from the broad areas of machine learning and deep learning.
Negation in A Language -- A Computational Approach for the Tonal Identification in Bodo Language -- Real-Time Detection of Natural Scene Assamese Texts using Deep Learning -- Development Of Directional Drilling Well Profile Design App Using Python -- Prediction and forecasting municipal solid waste generation of Northeastern cities by retrofitting ML models of Guwahati, India.
Keywords: Artificial intelligence; Artificial intelligence -- Data processing; Natural language processing (Computer science).; Speech processing systems; Signal processing; Artificial Intelligence; Data Science; Natural Language Processing (NLP).; Speech and Audio Processing